Spatial and temporal development of microorganisms and the effect of clogging in up-flow sand filter - Farhana Abd Lahin; Rosalam Sarbatly; Chiam Chel Ken (Universitas Indonesia, 2024)
Up-flow sand filtration is an excellent alternative to point-of-use treatment for rural water supply. However, the sites and interval of microorganism growth in filter beds and the effect on bioclogging remain unknown. This study aimed to assess microorganism growth based on biological activity levels using Dissolved Oxygen (DO) consumption and Field Emission Scanning Electron Microscopy (FE-SEM) imaging in various zones of the filter bed. Additionally, pressure drop was monitored to evaluate bio-clogging. The results showed that microorganism activities differed within the 0.50 m up-flow sand filter bed during 8 weeks of acclimatization. Exponential growth started after day 35, and DO levels declined to a minimum of 2 mg/L at 0.10 m bed height (measured from the bottom) after day 46. At 0.30 m and 0.50 m height, the DO decreased to 0.8 mg/L and 0.3 mg/L after days 35 and 46, respectively. FE-SEM images confirmed microorganism growth on samples from 0.1 m after 4 weeks of acclimatization. Substantial growth was seen on samples of 0.10 and 0.30 m height at 8 weeks, while lesser growth was observed on samples of 0.50 m. The pressure drop showed no significant increase, signifying that clogging did not occur during the 135- day operational period. In conclusion, the up-flow configuration prevented bio-clogging in sand filters, reducing maintenance requirements.